Molecular identification of Theileria and Babesia in sheep and goats in the Black Sea Region in Turkey - Aydin, Mehmet Fatih; Aktas, Munir; Dumanli, Nazir (Springer, 2013)
This study was carried out to investigate presence and distribution of Theileria and Babesia species via microscopic examination and reverse line blotting (RLB) techniques in sheep and goats in the Black Sea region of Turkey. For this purpose, 1,128 blood samples (869 sheep and 259 goats) were collected by active surveillance from sheep and goats in different provinces of various cities in the region in the years 2010 and 2011. Smears were prepared from the blood samples, stained with Giemsa, and examined under the light microscope for Theileria and Babesia piroplasms. The genomic DNAs were extracted from blood samples. The length of 360-430-bp fragment in the variable V4 region of 18S SSU rRNA gene of Theileria and Babesia species was amplified using the gDNAs. The polymerase chain reaction products were hybridized to the membrane-connected species-specific probes. A total of 38 animals (3.37 %) including 34 sheep (3.91 %) and 4 goats (1.54 %) were found to be positive for Theileria spp. piroplasms in microscopic examination of smears while Babesia spp. piroplasm could not detected. Infection rates were 34.64 % in sheep, 10.04 % in goats, and totally 28.99 % for Theileria ovis while 0.58 % in sheep and totally 0.44 % for Babesia ovis. However, Theileria sp. OT3 was detected in 2.65 % of sheep and 2.04 % of all animals; besides Theileria sp., MK had 0.58 % prevalence in sheep and 0.77 % in goats, with a total 0.62 % with RLB. Although T. ovis and Theileria sp. MK were determined in both sheep and goats, B. ovis and Theileria sp. OT3 were observed only in the sheep. These results provide the first detailed molecular data for sheep and goat theileriosis and babesiosis in the region.
Keywords: Small Ruminants; Genetic Diversity; Differentiation; Infection; Parasites; Transmission; Prevalence; Ticks; Ovis; East